PARTICIPATION OF UKRAINE IN INTERNATIONAL MIGRATION PROCESSES UNDER THE CONDITIONS OF WAR - TUNITSKA, Yuliia; TUNITSKYI, Nazarii; DAVIDENKO, Daryna; ZIZA, Maxim (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The acceleration of migration processes in the modern globalized world is taking place against the background of population growth, aggravation of climatic and economic crises and geopolitical conflicts, which forces the international community to take decisive steps in the direction of overcoming the consequences of using refugees for the purpose of political pressure on countries, providing assistance to forced migrants. The beginning of the large-scale invasion radically changed the structure and directions of movement of emigrants from Ukraine, deepened the problem of the outflow of highly qualified personnel, in particular to the EU. Therefore, overcoming the largest migration crisis in the world since the Second World War and the return of labor resources to the country depends on the improvement of the national migration policy, which will take into account international standards in the field of migration, international protection, employment and integration, as well as provide an opportunity to specify the directions of support for Ukrainians according to the border. The article defines the place of Ukraine in modern global migration processes, which take place in the conditions of financial crises bursts, political and military conflicts. Changes in the characteristic features of immigration and emigration of Ukraine since independence, in particular during the pre-war period and the period of the COVID-19 pandemic, are outlined. Absolute and relative indicators of international population migration in 2002–2021 were analyzed. The peculiarities of the forced migration crisis in connection with the large-scale invasion of the russian federation, in particular the change in the geographical structure of migration flows from Ukraine, the aggravation of the problem of the labor resources outflow, have been studied. Ukraine’s strategic partners among the EU and OECD countries in the field of wartime migration have been identified, taking into account the number of admitted forced emigrants, the amount of financial assistance provided to them, and the implementation of migration policy adaptation measures.